DNA damage and decrease of cellular oxidase activity in piglet sertoli cells exposed to gossypol - Ming Zhang; Hui Yuan; Zuping He; Liyun Yuan; Jine Yi; Sijun Deng; Li Zhu; Chengzhi Guo (African Journal of Pig Farming, 2015)
The study was designated to explore the toxic effects of gossypol on piglet sertoli cells. Sertoli cells were isolated from piglet testes using a two-step enzyme digestion and followed by differential plating. Piglet sertoli cells were cultured and classified into five groups, that is, group A, the control without gossypol, group B with 2.5 μg/ml gossypol, group C with 5 μg/ml gossypol, group D with 10 μg/ml gossypol and group E with 20 μg/ml gossypol. We found that sertoli cells’ growth was inhibited by gossypol at dose 2.5 μg/ml when compared with the control group. The oxidase activity of sertoli cell also decreased at 2.5 μg/m gossypol. Moreover, DNA damage of sertoli cells was observed at 5 μg/ml gossypol. Putting this into consideration, our study suggests that exposure of gossypol to sertoli cells leads to an inhibition of sertoli cell growth and oxidase activity of sertoli cells at a low concentration, whereas gossypol results in DNA damage of sertoli cells at a higher concentration.